Upaya Meningkatkan Keterampilan Membaca Permulaan Melalui Media Flashcard Kelas 1 Sekolah Dasar Di Gunungkidul Yogyakarta - Utami, Nadia Mega; Utomo, Khoirul Budi (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This study aims to improve the beginning reading skills of grade 1 elementary school students through the use of flashcard learning media. This study uses a Classroom Action Research (CAR) approach which is implemented in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of the study were seven grade 1 students, consisting of five male students and two female students. The results of the study showed a significant increase in students' reading skills after the application of flashcards. In the pre-cycle stage, only one student was able to read fluently, while in Cycle 1 there were two students who showed improvement, although the other five students still had difficulty in recognizing letters and words. Evaluation at the end of Cycle 1 showed that flashcards were effective in attracting students' attention and increasing their motivation to learn to read. However, further practice is still needed for students who have difficulty. This study concludes that the use of flashcard media can be an effective alternative to improve the beginning reading skills of grade 1 elementary school students.